Hydrogen Sulfide Increases Nitric Oxide Production and Subsequent S-Nitrosylation in Endothelial Cells - Ping-Ho Chen; Yaw-Syan Fu; Yun-Ming Wang; Kun-Han Yang; Danny Ling Wang; Bin Huang (The Scientific World Journal)
Hydrogen sulfide (H2S) and nitric oxide (NO), two endogenous gaseous molecules in endothelial cells, got increased attention with respect to their protective roles in the cardiovascular system. However, the details of the signaling pathways between H2S and NO in endothelia cells remain unclear. In this study, a treatment with NaHS profoundly increased the expression and the activity of endothelial nitric oxide synthase. Elevated gaseous NO levels were observed by a novel and specific fluorescent probe, 5-amino-2-(6-hydroxy-3-oxo-3H-xanthen-9-yl)benzoic acid methyl ester (FA-OMe), and quantified by flow cytometry. Further study indicated an increase of upstream regulator for eNOS activation, AMP-activated protein kinase (AMPK), and protein kinase B (Akt). By using a biotin switch, the level of NO-mediated protein S-nitrosylation was also enhanced. However, with the addition of the NO donor, NOC-18, the expressions of cystathionine-γ-lyase, cystathionine-β-synthase, and 3-mercaptopyruvate sulfurtransferase were not changed. The level of H2S was also monitored by a new designed fluorescent probe, 4-nitro-7-thiocyanatobenz-2-oxa-1,3-diazole (NBD-SCN) with high specificity. Therefore, NO did not reciprocally increase the expression of H2S-generating enzymes and the H2S level. The present study provides an integrated insight of cellular responses to H2S and NO from protein expression to gaseous molecule generation, which indicates the upstream role of H2S in modulating NO production and protein S-nitrosylation.